Low loss and low temperature sintering of Li3Mg2NbO6 ceramics for LTCC applications. (24th May 2019) - Wang, Pinglu; Zhu, Meng; Chen, Yang; Xie, Fei; Xiao, Nan; Hou, Bei; Lu, Wei; Jiang, Fuwei; Zheng, Wanze
Abstract: We fabricated the low loss Li3 Mg2 NbO6 - x V2 O5 (x = 0.25–1.25 wt%)ceramics by the solid-state reaction procedure and discussed the impacts of V2 O5 addition on the phase structure, sintering characteristics, microstructure, grain growth, grain size and microwave dielectric characterizations of Li3 Mg2 NbO6 - x V2 O5 ceramics. Single-phase Li3 Mg2 NbO6 orthorhombic structure was obtained for all compositions and substitution of V 5+ ions for Nb 5+ ions occurred. Homogeneous and dense microstructures with grain size of ∼11.2 μ m could be observed when sintered at 925 °C, indicating that suitable V2 O5 addition content promoted the grain growth. The relative permittivity was associated with the relative density and the Q × f value was correlated to the grain size and relative density. The τ f value was relevant to the porosity corrected relative permittivity. Remarkable microwave dielectric properties: ε r = 15.1, Q × f = 91, 000 GHz (9.76 GHz) and τ f = −24 ppm °C −1 were acquired for the samples with x = 1 wt%, indicating a potential for LTCC applications.